Clinical outcomes of Enhanced Recovery after Surgery Protocol for Hepato- pancreato- biliary Surgery; A Five-Year Experience from a Hellenic Oncological Hospital ERAS protocol and HPB surgery - Kapritsou, Maria; Alexandrou, Evan; Konstantinou, Evangelos A; Giannakopoulou, Margarita; Fyrfiris, Nikolaos; Korkolis, Dimitrios P (Health & Research Journal, 2022)
Background: The development of enhanced recovery after surgery protocols (ERAS) for surgical intervention has contributed to reducing hospital length of stay and improved patient outcomes. Aim of the study was the assessment of the recovery time and cost-effectiveness of an ERAS protocol in oncological patients undergoing hepato- pancreato- biliary surgery (HPB) compared to conventional (CON) care. Methods: This prospective, open label, randomized trial, enrolled 283 patients who required hepatectomy or pancreatoduodenectomy. Eligible patients were stratified into hepatectomy or pancreatectomy groups then, randomly assigned to ERAS protocol (intervention) or CON care (control). The primary outcome of interest was post-operative recovery time (composite of; time to mobilization and oral intake) and secondary outcomes were cost effectiveness, dependance on post-operative opioids and post-operative complications (using the Clavien- Dindo classification). Results: The rate of complications for the patients underwent hepatectomy and treated in ERAS group was 18.18% compared to CON group, which was 40.9%. Whilst, of complications for the patients underwent pancreatectomy and treated in ERAS group was 15.94% compared to CON group, which was 38.2%. Conclusions: The ERAS protocol in this study significantly improved post-operative recovery time, reduced opioid dependance and reduced post-operative complications in patients undergoing HPB surgery.